2015
DOI: 10.2217/rme.15.59
|View full text |Cite
|
Sign up to set email alerts
|

Using the Cost–Effectiveness of Allogeneic Islet Transplantation to Inform Induced Pluripotent Stem Cell-Derived β-Cell Therapy Reimbursement

Abstract: It was determined that, over a 9-year time horizon, islet transplantation would become cost saving and 'dominate' the comparator. Over a 20-year time horizon, islet transplantation would incur significant cost savings over the comparator (GB£59,000). Finally, assuming a similar cost of goods to islet transplantation and a lack of requirement for immunosuppression, a human induced pluripotent stem cell-derived β-cell therapy would dominate the comparator over an 8-year time horizon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Stem cell-derived b-cell therapy overcomes the barrier of limited donor availability, while also possibly representing a more costeffective therapy compared to exogenous insulin. Although the future cost of stem cell-derived b-cell therapy is unknown, a speculative cost-effectiveness analysis from an early health technology assessment study (29) calculates that 8-9 years after transplantation both cadaveric islet transplantation and stem cellderived b-cell transplantation would be more cost-effective than exogenous insulin therapy. This calculation assumes that the manufacturing costs of stem cell-derived b cells will be similar to the costs necessary to isolate cadaveric islets.…”
Section: Why the Need For Stem-cell Based Therapy In Diabetes?mentioning
confidence: 99%
“…Stem cell-derived b-cell therapy overcomes the barrier of limited donor availability, while also possibly representing a more costeffective therapy compared to exogenous insulin. Although the future cost of stem cell-derived b-cell therapy is unknown, a speculative cost-effectiveness analysis from an early health technology assessment study (29) calculates that 8-9 years after transplantation both cadaveric islet transplantation and stem cellderived b-cell transplantation would be more cost-effective than exogenous insulin therapy. This calculation assumes that the manufacturing costs of stem cell-derived b cells will be similar to the costs necessary to isolate cadaveric islets.…”
Section: Why the Need For Stem-cell Based Therapy In Diabetes?mentioning
confidence: 99%
“…Furthermore, health economic simulation based on initial clinical experience with cell therapy in Parkinson's disease supports realizable cost-saving within a decade in the treatment of early onset degenerative conditions 90,91 . Similarly, stem cellderived ß cell therapy for diabetes has been predicted to provide cost-benefit over life-long insulin therapy within an 8-year horizon 92 . Notwithstanding, health economic evaluation of advanced therapies remains limited and inconclusive [93][94][95] .…”
Section: Economic Considerationmentioning
confidence: 99%
“…Cost‐utility analyses of IT have shown that IT is cost‐effective, albeit at high willingness‐to‐pay thresholds (e.g. Can$100 000), and long‐term 37–39 . These studies have compared IT to insulin therapy, which are not mutually exclusive or equivalent, and will have to be updated as procedural and immunosuppression costs decrease, as reports on long‐term outcomes become more prevalent, and as stem cell therapies enter the clinic 39 .…”
Section: Indications and Procedural Considerationsmentioning
confidence: 99%